2016
DOI: 10.18632/oncotarget.10052
|View full text |Cite
|
Sign up to set email alerts
|

Network-based identification of microRNAs as potential pharmacogenomic biomarkers for anticancer drugs

Abstract: As the recent development of high-throughput technologies in cancer pharmacogenomics, there is an urgent need to develop new computational approaches for comprehensive identification of new pharmacogenomic biomarkers, such as microRNAs (miRNAs). In this study, a network-based framework, namely the SMiR-NBI model, was developed to prioritize miRNAs as potential biomarkers characterizing treatment responses of anticancer drugs on the basis of a heterogeneous network connecting drugs, miRNAs and genes. A high are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 57 publications
(88 reference statements)
0
83
0
Order By: Relevance
“…Then the two obtained networks are compared to highlight cancer-associated microRNAs (44). Variants of the network reconstruction procedure were also explored, based on measures different from correlation (45), or combining miRNA expression with alternative sources of information as drug response and miRNA targets (46). In this last case, the approach led to the identification of 11 oncomiRs (e.g.…”
Section: Methods Based On Mirna Expression Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Then the two obtained networks are compared to highlight cancer-associated microRNAs (44). Variants of the network reconstruction procedure were also explored, based on measures different from correlation (45), or combining miRNA expression with alternative sources of information as drug response and miRNA targets (46). In this last case, the approach led to the identification of 11 oncomiRs (e.g.…”
Section: Methods Based On Mirna Expression Datamentioning
confidence: 99%
“…Some computational methods have then been designed to predict genes and pathway jointly regulated by a set of microRNAs. The networkbased methods that we have described above for the prioritization of differentially expressed microRNAs (41,(44)(45)(46) represent a first example of such kind of methodologies. Given that from the structure of the miRNA-miRNA network, used to prioritize miRNAs, it is also possible to elucidate their combined effect.…”
Section: Methods Considering the Mirna-mirna Synergistic Effectmentioning
confidence: 99%
“…They identified optimally subnetwork markers in the protein–protein interaction network based on minimizing the distances of samples from the same class while maximizing the distances of samples from different classes. Furthermore, another group proposed a network‐based framework, namely the SMiR‐NBI model, to prioritize miRNAs as potential biomarkers characterizing treatment responses of anticancer drugs based on the heterogeneous network connecting drugs, miRNAs and genes . Although the continuous optimization of the methods improved the performance of the predictors, the network marker dissection was only based on gene expression and is insufficient to interpret complex mechanisms that underlie chemotherapy resistance at multiple levels.…”
mentioning
confidence: 99%
“…We performed LOOCV based on the known SMiR associations in the SM2miRdatabase (Liu et al, 2012) to measure the performance of RWNS. RWNS was compared with two stateof-the-art SMiR prediction methods: SMiR-NBI (Li et al, 2016) and TLHNSMMA (Qu et al, 2018) in LOOCV. SMiR-NBI designed a network-based inference method to identify new SMiR associations.…”
Section: Performance Evaluation Under Loocvmentioning
confidence: 99%
“…smiRN-AD integrated gene expression data from bioactive small molecule perturbation and Alzheimer's disease-related miRNA regulation. Li et al (2016) designed a network-based miRNA pharmacogenomic model, SMiR-NBI, integrating relevant biological information, including drugs, miRNAs, genes, and a network-based inference approach into a unified framework. SMiR-NBI effectively discovered potential response mechanisms of anticancer drugs targeting miRNAs and found that miRNAs may be underlying pharmacogenomic biomarkers in cancers.…”
Section: Introductionmentioning
confidence: 99%